The evolution of conceptual modeling of “magic” and “medical” metaphors in Ancient Greek rhetorical and philosophical discourse - Поліщук (Шадчина), Анна Сергіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
Using the theory of conceptual metaphor as a theoretical framework, this paper explores the metaphorical use of the magical and  / or medical concepts in Gorgias, Empedocles, Plato, Dionysius of Halicarnassus and Pseudo-Longinus. It examines how a deep level of the cognitive image of magic and medicine echoes ‘frames’ that constitute the target domain of rhetoric in the Ancient Greek language. This study focuses on Gorgias’ speech “Encomium of Helen” as both the one of the earliest and most representative in the use of such conceptual metaphors within Ancient Greek rhetorical and philosophical discourses. Judging by the text of Gorgias and other works of Ancient Greek literature, the slots of the source domain of the metaphor intersect with the etymological bases of the magic lexicon (“power”; “sound suggestion” and “formation of visual images”), and are supplemented by new ones (“unnatural influence”, “efficiency”; “carelessness of target audience”, “change of emotional and cognitive state”). This Gorgias model of rhetorical influence found its fruitful application in Plato and rhetoricians of the Hellenistic-Roman period, though with diametrically opposite axiological meanings: negative in Plato and positive in Dionysius of Halicarnassus and Pseudo-Longinus. Indeed, in Hellenistic rhetorical theory, negatively marked slots of the metaphorical frame disappeared (probably because of the influence of the then-current views in medicine), as well as concepts with ambivalent treatment, such as φάρμακον. Finally, it seems that among the above-mentioned authors the only one who has paid attention to the methodological similarity between rhetoric and medicine, given the medical terms and metaphors used by Gorgias, was Plato.